2018
DOI: 10.1021/acs.jafc.8b00313
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Activity Relationship Modeling Coupled with Molecular Docking Analysis in Screening of Angiotensin I-Converting Enzyme Inhibitory Peptides from Qula Casein Hydrolysates Obtained by Two-Enzyme Combination Hydrolysis

Abstract: In this study, Qula casein derived from yak milk casein was hydrolyzed using a two-enzyme combination approach, and high angiotensin I-converting enzyme (ACE) inhibitory activity peptides were screened by quantitative structure-activity relationship (QSAR) modeling integrated with molecular docking analysis. Hydrolysates (<3 kDa) derived from combinations of thermolysin + alcalase and thermolysin + proteinase K demonstrated high ACE inhibitory activities. Peptide sequences in hydrolysates derived from these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Bioactive peptides encrypted within the natural food protein are supposed to be released by enzymolysis to exert their biological function. A number of food processing enzymes were previously used for the generation of bioactive peptides from a variety of natural sources (Fu, Wu, Zhu, & Xiao, ; Lin, Zhang, Han, Meng, et al, ). In our study, three commercial plant proteases papain, ficin, and stem bromelain were applied, respectively, to the selected quinoa protein sequences by “Enzyme(s) action” of BIOPEP (Appendix S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactive peptides encrypted within the natural food protein are supposed to be released by enzymolysis to exert their biological function. A number of food processing enzymes were previously used for the generation of bioactive peptides from a variety of natural sources (Fu, Wu, Zhu, & Xiao, ; Lin, Zhang, Han, Meng, et al, ). In our study, three commercial plant proteases papain, ficin, and stem bromelain were applied, respectively, to the selected quinoa protein sequences by “Enzyme(s) action” of BIOPEP (Appendix S2).…”
Section: Resultsmentioning
confidence: 99%
“…BIOPEP database, providing collection of sequences (proteins, bioactive peptides, allergenic proteins, and sensory peptides), can be used to predict biological activities about a protein sequence, and to estimate the release of bioactive peptides by proteolysis simulation using certain proteases (Minkiewicz, Dziuba, Iwaniak, Dziuba, & Darewicz, ). This in silico tools has been successfully applied in the investigation of bioactive peptides from different sources, including animal products, plant products, and seafood products, such as bovine meat proteins (Minkiewicz, Dziuba, & Michalska, ), porcine myofibrillar proteins (Kęska & Stadnik, ), yak milk casein (Lin et al, ), cereal storage proteins (Cavazos & de Mejia, ), oilseed proteins (Han, Maycock, Murray, & Boesch, ), giant grouper roe proteins (Panjaitan, Gomez, & Chang, ), and portuguese oyster proteins (Gomez, Peralta, Tejano, & Chang, ). In addition, online tool PeptideRanker has the function of predicting the potential bioactive index of peptides, and ToxinPred has been developed to predict the toxicity of peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they explored their interaction mechanisms and bonding configurations with ACE by using docking and molecular dynamics (MD) simulations. In other interesting report, Lin et al [32] hydrolyzed Qula casein derived from yak milk casein and screened high ACE inhibitory activity peptides by using quantitative structure-activity relationship (QSAR) modeling integrated with molecular docking analysis. On the basis of the QSAR modeling predictions, authors selected a total of 16 peptides for molecular docking analysis and their docking study revealed that four of the peptides (KFPQY, MPFPKYP, MFPPQ, and QWQVL) bound the active site of ACE.…”
Section: Molecular Modeling Applied To the Study Of Ace Inhibitors Inmentioning
confidence: 99%
“…From the perspective of cheese processing, milk with such high levels of dry matter is well suited for cheese making. Every year, more than 1.6 million tonnes of yak milk are produced in the southwest region of China, including the Qinghai, Gansu, Sichuan, and Tibet areas (Lin et al, 2018). However, little of the milk was processed into cheese due to the diet habits of local people, and the cheese making properties of yak milk have seldom been reported.…”
Section: Introductionmentioning
confidence: 99%